Knowledge and attitude about risky pregnancy among student - Suci Musvita Ayu; S. Lindawati; Thoharoh Halimatusa’diyah (International Journal of Evaluation and Research in Education (IJERE), 2020)
This study was conducted examine the effect of counseling on the increasing knowledge and attitudes about risky pregnancies at Muhammadiyah 1 Vocational High School in Wonosobo, Indonesia. This research was quasi-experimental research employed quasi experiment design with one group pretest-post-test design. Measurements were made before and after treatment, by doing a pre-test and post-test. Sample sie in this study was 108 students. The instrument in this study is the questionnaire. The results of the knowledge variable showed a significant value 0.003. There is an effect of reproductive health counseling on increasing knowledge and attitudes about risky.